Social Media Engagement and Its Impact on Learning Achievement in Islamic Religious Education - Ridwan, Ridwan; Abbas, Hijrahwaty (Educational Journal of Learning Technology, 2026)
This study examines the impact of social media on the learning outcomes of Islamic Religious Education for grade XI students at SMA Negeri 4 Palopo. The research aims to identify how social media influences the learning process and how its use affects students’ academic achievement. This study employs a descriptive qualitative approach using primary and secondary data obtained through observation, interviews, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results show that social media provides both positive and negative impacts. Positive impacts include broader access to religious information, increased motivation to learn, and more varied learning experiences aligned with the digital generation. Negative impacts include decreased concentration, the tendency to use social media solely for entertainment, and technical barriers during learning. Overall, social media exerts a dual influence, underscoring the need for digital literacy and appropriate guidance to ensure learning objectives are achieved effectively.